The Devil’s Bargain: Educational Research and the Teacher - Goodson, Ivor F. (Education Policy Analysis Archives, 1993)
The concern of this paper is to explore why it is that so much educational research has tended to be manifestly irrelevant to the teacher. A secondary question is how that irrelevance has been structured and maintained over the years. There are I think three particularly acute problems. Firstly the role of the older foundational disciplines in studying education. Secondly, the role of faculties of education generally. Thirdly, related to the decline of foundational disciplines and the crisis in the faculties of education, the dangers implicit in too hasty an embrace of the panacea of more practical study of education.